2010
DOI: 10.1007/s10212-010-0040-7
|View full text |Cite
|
Sign up to set email alerts
|

Fifth graders metacognitive knowledge: general or domain-specific?

Abstract: The purpose of the present study was to investigate the structure of metacognitive knowledge in fifth grade pupils and its relation to school achievement. Since the structure of metacognitive knowledge is controversially discussed with little empirical evidence for either its domain specificity or its domain transferability, the debate remains somewhat hypothetical up to date. In theory it is assumed that the development of metacognitive knowledge begins highly domain and situation-specific and becomes more fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0
10

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 31 publications
4
42
0
10
Order By: Relevance
“…This finding confirms the results of a study conducted by Short, Schatschneider, and Friebert (1993), who found that there is a development of strategy knowledge with increasing grade level in math. In addition, our finding aligns with previous longitudinal studies in other domains (Neuenhaus et al, 2011;Schneider, 2010). In light of these results, we argue that students grow in their cognitive awareness of problem-solving strategies.…”
Section: Latent Means Across Gradessupporting
confidence: 92%
See 1 more Smart Citation
“…This finding confirms the results of a study conducted by Short, Schatschneider, and Friebert (1993), who found that there is a development of strategy knowledge with increasing grade level in math. In addition, our finding aligns with previous longitudinal studies in other domains (Neuenhaus et al, 2011;Schneider, 2010). In light of these results, we argue that students grow in their cognitive awareness of problem-solving strategies.…”
Section: Latent Means Across Gradessupporting
confidence: 92%
“…Together with Kaberman and Dori (2009), Lingel, Neuenhaus, Artelt, and Schneider (2010), and Neuenhaus et al (2011), we argue that there is a domain-specific component. To address this issue, further research should analyze the structure of the construct across further domains .…”
Section: Assessment Of Strategy Knowledgementioning
confidence: 70%
“…Further, the measurements of the frequency of strategy use and metacognitive strategy knowledge are limited to the context of tackling complex and larger essays at school. As shown by Neuenhaus et al (2010), metacognitive strategy knowledge is to a certain degree domain specific. Therefore, future studies might assess different types of metacognitive strategy knowledge.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, the metacognitive strategy knowledge test used in this study assessed the students' metacognitive strategy knowledge in the context of tackling larger essays or projects that they encounter at school (Maag Merki, Ramseier, & Karlen, 2013). The design of this test is related to similar test instruments developed for other schooling levels and domains (e.g., H€ andel, Artelt, & Weinert, 2013;Neuenhaus, Artelt, Lingel, & Schneider, 2010). Seven different scenarios provide a description of learning situations related to the context of tackling larger essays, taking the process structures of SRL into account (Maag Merki, Ramseier, & Karlen, 2013).…”
Section: Instrumentsmentioning
confidence: 99%
“…By contrast, most researchers concerned with cross-curricular competencies, assume that generally strategies and metacognition can be transferred to other situations (cf. Artelt, Baumert, Julius-McElvany, & Peschar, 2003;Neuenhaus, Artelt, Lingel, & Schneider, 2011). Zimmerman (1989) describes self-regulated learners as follows: "Students can be described as self-regulated to the degree that they are metacognitively, motivationally, and behaviorally active participants in their own learning process" (p. 4).…”
Section: Introductionmentioning
confidence: 99%